Development of UV-Vis spectroscopic method for determining effect of solvent on solubility of Vitamin C and Vitamin E - Anni, Raisa Thasnim (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2020.